Correlation between market-to-book value and financial ratios of South African companies. - Shewdin, Riaan (My University, 2017)
This research study examines the relationship between JSE main board listed companies accounting financial ratios and the level of shareholder wealth created by these companies at their financial year end, with the aim of identifying whether this relationship is consistent across industry sectors. The Market-to-Book (MTB) ratio is used to measure shareholder wealth, as this measure incorporates the funds that shareholders‘ have had to invest in the company in obtaining current market value level of their shareholding in the company. The accounting financial ratios studied include Profitability, Performance, Asset Efficiency, Capital Structure, and Liquidity ratios. Standardised financial statements and daily equity prices for JSE main board listed companies across nine industry sectors were collected for the 2001-2010 period, from which MTB ratios and accounting financial ratios were calculated. To measure the relationship between companies accounting financial ratios and the level of shareholder wealth created by these companies, the relationship between the MTB ratio and accounting financial ratios for each industry sector were tested through: multiple correlation analysis, testing the strength of the relationship between the MTB ratio and the combined effect of each facet of a company‘s financial; and bivariate correlation analysis testing the strength of the relationship between individual accounting financial ratio and the MTB ratio. This study demonstrated that, with the exception of the Cyclical Consumer Goods industry sector, a company‘s accounting financial ratios are related to its MTB ratio. The strength of this relationship, as well as the individual accounting financial ratios that displayed the greatest substantive significant relationship to the MTB ratio were found to differ across industry sectors, confirming that financial structural differences are present across industry sectors. A company‘s management team should therefore focus on consistently driving improved performance of those financial ratios most related to the MTB ratio in an effort to ensure that wealth for shareholders‘ is constantly be created.
MBA Thesis
Keywords: Johannesburg Stock Exchange,Stocks -- Prices -- South Africa,Corporations -- Valuation -- South Africa,Corporations -- Finance -- Mathematical models.